Narcissism in the context of depressiveness and happiness. Self-esteem and neuroticism as mediators. - Adam Łojan (Rozprawy Społeczne)
Abstract The article is focused on relationships between the two types of narcissism and depressiveness as well as happiness. It seems important issue since many researchers claim that modern societies experience the epidemy of narcissism, which moreover, cannot be perceived as a homogeneous phenomenon.